Visualizing Lifestyle and Fashion Behavior in Kevin Kwan’s Novel Crazy Rich Asians, Represented in the Film by Jon M. Chu - Zahra , Audesza Rizkia; Iman, Diah Tyahaya (English Department, Faculty of Humanities, Andalas University, 2024)
This study compares the novel Crazy Rich Asians by Kevin Kwan (2013) and the film adaptation of the same title, Crazy Rich Asians, by director Jon M. Chu (2018). Using the adaptation theory by Linda Hutcheon, this thesis examines how Jon M. Chu describes lifestyle and fashion behavior by looking at the three points of social stratification proposed by Max Weber. This research was carried out using a qualitative method. We argue that the lifestyle of upper-class people and fashion behavior in the novel are illuminated luxuriously on the screen. The atmosphere in the film of the lifestyle and fashion behavior strengthens the arrogant manners of the elite class. The novel’s social dynamics and romantic drama have been exposed with a strong ambiance for the cinematic experience for the audience.